2022
DOI: 10.1002/anie.202213405
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Enzyme Immobilization by Covalent Organic Frameworks

Abstract: Enzyme immobilization is a widely reported method to favor the applicability of enzymes by enhancing their stability and re‐usability. Among the various existing solid supports and immobilization strategies, the in situ encapsulation of enzymes within crystalline porous matrices is a powerful tool to design biohybrids with a stable and protected catalytic activity. However, to date, only a few metal–organic frameworks (MOFs) and hydrogen‐bonded organic frameworks (HOFs) have been reported. Excitingly, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…hydrophobic interaction, 20,21 electrostatic interaction, 22 etc .) and chemical bonding (including hydrogen bonding, 23 covalent binding, 24,25 etc .). Enzymes can be immobilized through physical adsorption by simply mixing the enzymes with suitable nanomaterials.…”
Section: Natural-enzyme Based Nanocomposites For Catalytic Biomedicinementioning
confidence: 99%
“…hydrophobic interaction, 20,21 electrostatic interaction, 22 etc .) and chemical bonding (including hydrogen bonding, 23 covalent binding, 24,25 etc .). Enzymes can be immobilized through physical adsorption by simply mixing the enzymes with suitable nanomaterials.…”
Section: Natural-enzyme Based Nanocomposites For Catalytic Biomedicinementioning
confidence: 99%
“…[17][18] In addition, the ordered porous structures and high surface area also endow COF materials with high mass transfer rate. [19][20][21][22] Therefore, COFs can work as a robust platform hosting metal NPs to realize highly-efficiency catalytic reactions. [23][24][25][26][27][28] Though the operation of conventional postmodification strategies is simple, the time-consuming COF preparation and the sequent lab-cost modification are inevitable, possibly resulting in destruction of COF structures and non-uniformity of the formed nanoscale particles.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of metal NPs inside COFs is believed to be precisely anchored and restricted in the confined microenvironment, exempting from agglomeration and deactivation after reduction [17–18] . In addition, the ordered porous structures and high surface area also endow COF materials with high mass transfer rate [19–22] . Therefore, COFs can work as a robust platform hosting metal NPs to realize highly‐efficiency catalytic reactions [23–28] .…”
Section: Introductionmentioning
confidence: 99%
“…3.5 Å) due to their high surface area, good stability, and room temperature synthesis conditions in the water phase. , However, when enzymes such as horseradish peroxidase (HRP), glucose oxidase (GOx), catalase, and lipase were immobilized within ZIF-8 structures, they demonstrated low activity (<50%) in comparison to free enzymes. Recent studies showed that growing MOFs can be used for in situ immobilization of enzymes via approaches such as co-precipitation and biomineralization. These approaches allow rapid formation of enzyme@MOF composites by a one-step reaction with high stability and activity. ,, Furthermore, a peptide-modulated MOF (ZIF-8) was used to immobilize HRP in situ via electrostatic interaction, with enhanced activity . However, beyond the MOF-based host matrix materials, the understanding of a confined enzyme environment and the mechanism of conformation and orientation changes are urgently needed …”
Section: Introductionmentioning
confidence: 99%